How do you solve using the completing the square method #x^2-4x+2=0#?

1 Answer
Apr 11, 2017

Answer:

#y=(x-2)^2-2#

Explanation:

The completing the square form is:
#y=(x+a)^2+b #

The "a" term will be equal to the middle term divided by two. I.e. #-4/2=-2#.

This means that you now have the following:

#y=(x-2)^2+b#

Because the completing the square form is equivalent to your original equation you have:

#x^2−4x+2=(x-2)^2+b#
#x^2−4x+2=x^2-4x+4+b# <-- I expanded the right-hand side
#b=-2# <--After simplifying you can find the "b"-term